Incidence, clinical, and imaging presentation of orbital metastasis over 20 years in a tertiary eye care center in Egypt - Mohamed A Eldesouky; Hazem A Elbedewy (Delta Journal of Ophthalmology, 2023)
Purpose The aim of this study was to review the demographic, clinical, and imaging features of Egyptian patients with orbital metastases. Patients and methods This is a retrospective study of 66 patients with orbital metastatic lesions over the last 20 years (January 2000–December 2019). The ophthalmological reports and radiological images of the included patients were reviewed. Results The study included 66 patients: 34 males and 32 females. The primary tumors were breast carcinoma in 25.8% of the patients, hepatocellular carcinoma in 15.2%, and cutaneous malignant melanoma in 7.6% of the patients. The most common primary tumor in children was neuroblastoma (58.3%). In 22 (33.3%) patients, there was no history of cancer, and the orbital metastatic lesion was the first presentation. Diplopia and limited ocular movements were the presenting feature in 38 (57.6%) patients, proptosis and/or globe displacement in 32 (48.5%) patients, blurred vision in 12 (18.2%) patients, pain in nine (13.6%) patients, enophthalmos in six (9.1%) cases, ptosis in five (7.6%) cases, and inflammatory manifestations in four (6.1%) patients. In 60 (91%) patients, the lesion was unilateral and only six (9%) cases had bilateral lesions. Orbital imaging showed infiltrative lesion in 36.4%, mass lesion in 33.3%, isolated muscle thickening in 10.6%, and bone changes in 39.4% of the patients. The observed incidence of orbital metastasis increased from 13.6% during 2000–2004 to 43.9% in 2015–2019. Conclusion The incidence of orbital metastatic lesions increased dramatically through the last two decades. Moreover, this may be underestimated due to undiagnosed small silent lesions. Breast carcinoma ranked as the first primary tumor followed by hepatocellular carcinoma, probably owing to the high prevalence of hepatitis C virus among the Egyptian population.